Barriers To Retention And Advancement Of Women In Technical Field: A Study Of American Multinational Corporations In Malaysia - Ramasamy, Vimaleswari K. (2018)
Talent shortage and scarcity of women’s participation in the workforce, has always been a concern globally for decades. Many actions taken by government and organisations in introducing policies and practices, to attract and enable women to strive in their career, but they have not yielded significant results. Although, there has been an increase of women’s participation in the workforce, it is at a much slower rate than anticipated and further, there is a sharp decline as their seniority increases. Specifically, in Malaysia the decline has not bounced back as seen in other countries in the region. This research, attempts to investigate and provide empirical data of the barriers faced by women in the technical field, in retaining and advancing into leadership roles at American based Multinational Corporations (MNCs) in Malaysia. Qualitative in-depth interviews with twenty-five women, adopting a four-quadrant framework and utilising a case-study approach were executed. This explored the attitude, perception and experiences of women in the technical field. A triangulation process was also conducted to affirm the narratives of the women with the efforts undertaken by the organisations, specifically in the availability of policies and practices. Caring for family, work life balance, gender stereotype, lack of development opportunities, low compensation and career contentment, were the barriers highlighted through this study. Indeed, the first four barriers were anticipated; however, the last two barriers were something that has not been vastly captured in past literatures, especially for Malaysia. Women needs of safe and discrimination free environment, flexibility to manage the dual role that they play, equal development opportunities and compensation that are not being fulfilled, are reflecting as the barriers seen above. Indeed, all of them stems from gender in-equality. Although, organisations have taken the efforts to attract, integrate and develop the women in the workforce, the policies and practices are not providing substantive equality that is desired. Women are still unable to have control to access and utilise resources that they need at the workplace; time, development and compensation. This study has revealed, that women with higher gender consciousness are able to drive change within their environment to push for substantive equality. Hence, cultivating gender consciousness within the workplace and society, is even more crucial in achieving substantive gender equality versus implementing more policies to attract, integrate and develop women in the workforce. Partnering with men in implementing the gender mainstream management and creating gender consciousness is the key to drive change that will enable substantive equality to be achieved.